Antiaromaticity to Aromaticity: From Boroles to 1, 2‐Azaborinines by Ring Expansion with Azides. Issue 32 (7th July 2014) - Braunschweig, Holger; Hörl, Christian; Mailänder, Lisa; Radacki, Krzysztof; Wahler, Johannes
Abstract Invited for the cover of this issue is the group of Holger Braunschweig at the Julius‐Maximilians‐Universität Würzburg (Germany). The image depicts the synthesis of 1, 2‐azaborinines by a ring‐expansion reaction of boroles with azides. Read the full text of the article at 10.1002/chem.201403101.